A new method for zone development observation for updraft rice husk gasification - Onthong, Kasemsil; Charoensuk, Jarruwat (My University, 2019)
Experiments were carried out with a new method for assessing an updraft gasification reactor. An attached side door enabled the investigation of zone development by stopping air supply at specific times, when the thickness of biomass, char, and ash layers were measured. Development in zone thicknesses of biomass, char, and ash with time associated with temperature distribution provided information about the speed of flame propagation inside the reactor. Initially, pyrolysis and volatile combustion occurred, as evidenced by the high mass loss rate and high growth rate of the char layer. Shrinkage in the char layer took place later, and this phenomenon was governed by char glowing, which was relatively slow in mass loss rate. Finally, the fully developed char layer was obtained. The results from four different air mass fluxes under updraft configuration were presented, showing the differences in layer development. Temperature profiles at each time step revealed that the location of peak temperature coincided with the location of ash-char interface for every air mass flux. This effect was due to the high energy release during the oxidation of fixed carbon.
Keywords: Biomass; Gasification; New method; Pyrolysis; Updraft; Volatile combustion